Uma proposta de abordagem para o ensino de cinemática relativística no ensino médio baseada em aprendizagem significativa de Ausubel - Poltronieri, Vinício Merçon (2017)
We teachers have experienced constant changes in the contents we teach. However, it is important to point out that not only the content but also the way we work must evolve. This dissertation presents a research which aims to highlight its importance and exemplify a way to apply the theories of renowned authors directly in the classroom. As a reference, we adopted the Meaningful Learning Theory of David Ausubel, from the point of view and Marco Antonio Moreira guidelines, and the chosen subject was the Relativistic Kinematics for high school students, from 1st to 3rd grade, which was applied as an extracurricular course at Charles Darwin Educational Center in Vitória-ES, between June and August 2016. We tried incorporating all the key elements of Meaningful Learning in class, such as prior knowledge, interactional products, subsumers and time of assimilation, in order to make the most complete and dynamic classes, checking the level of understanding of students throughout the course. Therefore, the main purpose of this dissertation is to encourage other teachers to deepen the study of educational theories, which show it is possible to improve their technique and certainly which show that even Kinematics Relativistic, famous for being anti-intuitive understanding, is not so difficult to learn if the progression of learning takes place in a logical and well-structured way.